5.27.7 Problems 601 to 700

Table 5.1179: Second order, Linear, non-homogeneous and constant coefficients

#

ODE

Mathematica

Maple

6487

\[ {}2 y^{\prime \prime }-7 y^{\prime }-4 y = {\mathrm e}^{3 x} \]

6488

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 54 x +18 \]

6489

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 100 \sin \left (4 x \right ) \]

6490

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 4 \sinh \left (x \right ) \]

6491

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 2 \cosh \left (2 x \right ) \]

6492

\[ {}y^{\prime \prime }-y^{\prime }+10 y = 20-{\mathrm e}^{2 x} \]

6493

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 2 \cos \left (x \right )^{2} \]

6494

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = x +{\mathrm e}^{2 x} \]

6495

\[ {}y^{\prime \prime }-2 y^{\prime }+3 y = x^{2}-1 \]

6496

\[ {}y^{\prime \prime }-9 y = {\mathrm e}^{3 x}+\sin \left (x \right ) \]

6497

\[ {}x^{\prime \prime }+4 x^{\prime }+3 x = {\mathrm e}^{-3 t} \]

6498

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 6 \sin \left (t \right ) \]

6499

\[ {}x^{\prime \prime }-3 x^{\prime }+2 x = \sin \left (t \right ) \]

6500

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 3 \sin \left (x \right ) \]

6501

\[ {}y^{\prime \prime }+6 y^{\prime }+10 y = 50 x \]

6502

\[ {}x^{\prime \prime }+2 x^{\prime }+2 x = 85 \sin \left (3 t \right ) \]

6503

\[ {}y^{\prime \prime } = 3 \sin \left (x \right )-4 y \]

6505

\[ {}x^{\prime \prime }+5 x^{\prime }+6 x = \cos \left (t \right ) \]

6506

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 4 x^{2} \]

6507

\[ {}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{3 x} \]

6508

\[ {}y^{\prime \prime }-y^{\prime }-2 y = \sin \left (2 x \right ) \]

6509

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 2 \sin \left (\frac {t}{2}\right )-\cos \left (\frac {t}{2}\right ) \]

6510

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 64 \,{\mathrm e}^{-t} \]

6511

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 50 t^{3}-36 t^{2}-63 t +18 \]

6513

\[ {}y^{\prime \prime } = 9 x^{2}+2 x -1 \]

6514

\[ {}y^{\prime \prime }-5 y = 2 \,{\mathrm e}^{5 x} \]

6518

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x^{2}-1 \]

6519

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 4 \,{\mathrm e}^{2 x} \]

6520

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 4 \cos \left (x \right ) \]

6521

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 3 \,{\mathrm e}^{x} \]

6522

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x \,{\mathrm e}^{x} \]

6529

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{x} \]

6530

\[ {}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{3 x} \]

6531

\[ {}x^{\prime \prime }+4 x = \sin \left (2 t \right )^{2} \]

6535

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{x^{5}} \]

6536

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

6537

\[ {}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{3 x} \]

6538

\[ {}y^{\prime \prime }-60 y^{\prime }-900 y = 5 \,{\mathrm e}^{10 x} \]

6539

\[ {}y^{\prime \prime }-7 y^{\prime } = -3 \]

6547

\[ {}y^{\prime \prime }-y = \sin \left (x \right ) \]

6548

\[ {}y^{\prime \prime }-y = {\mathrm e}^{x} \]

6549

\[ {}y^{\prime \prime }+2 y^{\prime }-3 y = \sin \left (2 x \right ) \]

6550

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

6552

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 3 \,{\mathrm e}^{-2 x} \]

6553

\[ {}y^{\prime \prime }+5 y^{\prime }-3 y = \operatorname {Heaviside}\left (x -4\right ) \]

6558

\[ {}q^{\prime \prime }+9 q^{\prime }+14 q = \frac {\sin \left (t \right )}{2} \]

6576

\[ {}y^{\prime \prime }-y = 4-x \]

6578

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 2 \left (1-x \right ) {\mathrm e}^{x} \]

6693

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{5 x} \]

6694

\[ {}y^{\prime \prime }+9 y = x \cos \left (x \right ) \]

6711

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 1 \]

6712

\[ {}y^{\prime \prime }-4 y^{\prime } = 5 \]

6716

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{2 x} \]

6717

\[ {}y^{\prime \prime }+y^{\prime }-2 y = -2 x^{2}+2 x +2 \]

6718

\[ {}y^{\prime \prime }-y = 4 x \,{\mathrm e}^{x} \]

6719

\[ {}y^{\prime \prime }-y = \sin \left (x \right )^{2} \]

6720

\[ {}y^{\prime \prime }-y = \frac {1}{\left (1+{\mathrm e}^{-x}\right )^{2}} \]

6721

\[ {}y^{\prime \prime }+y = \csc \left (x \right ) \]

6722

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \sin \left ({\mathrm e}^{-x}\right ) \]

6723

\[ {}y^{\prime \prime }+y = \csc \left (x \right ) \]

6724

\[ {}y^{\prime \prime }+4 y = 4 \sec \left (x \right )^{2} \]

6725

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = \frac {1}{1+{\mathrm e}^{-x}} \]

6726

\[ {}y^{\prime \prime }-y = {\mathrm e}^{-x} \sin \left ({\mathrm e}^{-x}\right )+\cos \left ({\mathrm e}^{-x}\right ) \]

6727

\[ {}y^{\prime \prime }-y = \frac {1}{\left (1+{\mathrm e}^{-x}\right )^{2}} \]

6728

\[ {}y^{\prime \prime }+2 y = 2+{\mathrm e}^{x} \]

6729

\[ {}y^{\prime \prime }-y = {\mathrm e}^{x} \sin \left (2 x \right ) \]

6730

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = x^{2}+\sin \left (x \right ) \]

6731

\[ {}y^{\prime \prime }-9 y = x +{\mathrm e}^{2 x}-\sin \left (2 x \right ) \]

6733

\[ {}y^{\prime \prime }+y = -2 \sin \left (x \right )+4 x \cos \left (x \right ) \]

6735

\[ {}y^{\prime \prime }+y^{\prime }+y = {\mathrm e}^{3 x}+6 \,{\mathrm e}^{x}-3 \,{\mathrm e}^{-2 x}+5 \]

6736

\[ {}y^{\prime \prime }-y = {\mathrm e}^{x} \]

6737

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = {\mathrm e}^{x}+{\mathrm e}^{2 x} x \]

6740

\[ {}y^{\prime \prime }+4 y = \sin \left (2 x \right ) \]

6741

\[ {}y^{\prime \prime }+5 y = \cos \left (\sqrt {5}\, x \right ) \]

6743

\[ {}y^{\prime \prime }-y = x^{2} \]

6744

\[ {}y^{\prime \prime }+2 y = x^{3}+x^{2}+{\mathrm e}^{-2 x}+\cos \left (3 x \right ) \]

6745

\[ {}y^{\prime \prime }-2 y^{\prime }-y = {\mathrm e}^{x} \cos \left (x \right ) \]

6746

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = \frac {{\mathrm e}^{2 x}}{x^{2}} \]

6747

\[ {}y^{\prime \prime }-y = x \,{\mathrm e}^{3 x} \]

6748

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = {\mathrm e}^{-2 x} \sec \left (x \right )^{2} \left (1+2 \tan \left (x \right )\right ) \]

6889

\[ {}y^{\prime \prime }+y = \tan \left (x \right ) \]

6917

\[ {}y^{\prime \prime }+4 y^{\prime }+6 y = 10 \]

6925

\[ {}y^{\prime \prime }+2 y^{\prime }+4 y = 5 \sin \left (t \right ) \]

6927

\[ {}y^{\prime \prime } = f \left (x \right ) \]

6986

\[ {}y^{\prime \prime }+9 y = 18 \]

6996

\[ {}y^{\prime \prime }+y = 2 \cos \left (x \right )-2 \sin \left (x \right ) \]

6997

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

7003

\[ {}y^{\prime \prime }+y = {\mathrm e}^{x^{2}} \]

7008

\[ {}y^{\prime \prime }+9 y = 5 \]

7010

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 6 x +4 \]

7011

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 6 x +4 \]

7012

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 6 x +4 \]

7013

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 6 x +4 \]

7350

\[ {}y^{\prime \prime }+9 y = 10 \,{\mathrm e}^{-t} \]

7352

\[ {}y^{\prime \prime }-6 y^{\prime }+5 y = 29 \cos \left (2 t \right ) \]

7353

\[ {}y^{\prime \prime }+7 y^{\prime }+12 y = 21 \,{\mathrm e}^{3 t} \]

7355

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = 6 t -8 \]

7356

\[ {}y^{\prime \prime }+\frac {y}{25} = \frac {t^{2}}{50} \]

7357

\[ {}y^{\prime \prime }+3 y^{\prime }+\frac {9 y}{4} = 9 t^{3}+64 \]

7360

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = 50 t -100 \]